ORGANIZATIONAL ADAPTABILITY AND COMPETITIVE STRATEGIES OF MANUFACTURING FIRMS IN NIGERIA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
The study's main goal is to ascertain how competitive strategies affect the firm adaptability of Nigerian listed manufacturing enterprises. A cross-sectional research approach was adopted in this study. Thirty (30) manufacturing firms listed in the Nigerian Stock Exchange's consumer, industrial, and healthcare sectors made up the sample. The basic random sampling technique was used. With the help of "Survey Monkey," a total of 396 sets of questionnaires were sent to respondents' email addresses; 300 of those sets were used for analysis. Before the Cronbach alpha test was used to assess the instrument's reliability, it underwent content and face validity assessments. OLS multiple regression, correlation, the Jacque Bera normality test, and descriptive statistics were among the statistical tools used in the data analysis because the study's main objective was to measure associations. The statistical program used in the study to examine the data was Stata version 13. The results show that there is a substantial positive correlation between the firm's adaptability and the focus strategy, differentiation strategy, and cost leadership strategy. The study comes to the conclusion that organizations must strictly follow the cost leadership approach in order to pursue competitive tactics. distinguishing strategy, focusing strategy, and monitoring using technology to improve manufacturing businesses' adaptability and longevity. In order to maintain a competitive edge over rivals and to take full use of its flexibility and inventiveness, management ought to implement a differentiation strategy.